Sorbic acid stress activates the Candida glabrata high osmolarity glycerol MAP kinase pathway - Jandric, Zeljkica; Gregori, Christa; Klopf, Eva; Radolf, Martin; Schüller, Christoph (Frontiers in Microbiology, 2013)
Weak organic acids such as sorbic acid are important food preservatives and powerful fungistatic agents. These compounds accumulate in the cytosol and disturb the cellular pH and energy homeostasis. Candida glabrata is in many aspects similar to Saccharomyces cerevisiae. However, with regard to confrontation to sorbic acid, two of the principal response pathways behave differently in Candida glabrata. In yeast, sorbic acid stress causes activation of many genes via the transcription factors Msn2 and Msn4. The C. glabrata homologues CgMsn2 and CgMsn4 are apparently not activated by sorbic acid. In contrast, in C. glabrata the high osmolarity glycerol (HOG) pathway is activated by sorbic acid. Here we show that the MAP kinase of the HOG pathway, CgHog1, becomes phosphorylated and has a function for weak acid stress resistance. Transcript profiling of weak acid treated C. glabrata cells suggests a broad and very similar response pattern of cells lacking CgHog1 compared to wild type which is over lapping with but distinct from S. cerevisiae. The PDR12 gene was the highest induced gene in both species, and required CgHog1 for full expression. Our results support flexibility of the response cues for general stress signaling pathways, even between closely related yeasts, and functional extension of a specific response pathway.